Patterns of niche contraction identify vital refuge areas for declining mammals. Issue 11 (20th August 2020) - von Takach, Brenton; Scheele, Ben C.; Moore, Harry; Murphy, Brett P.; Banks, Sam C.
Abstract: Aim: Investigation of realized niche contraction in declining species can help us understand how and where threats are being either mediated or tolerated across landscapes. It also provides insights into species' sensitivity to environmental change that are unable to be identified through analysis of declines in range size or abundance alone. Here, we apply the recently proposed "niche reduction hypothesis" to investigate relationships between trends in niche breadth and geographic distribution of declining species. Location: Northern Australia. Methods: We compare and contrast contemporary and historical data sets to examine the relationship between extent of occurrence (EOO) and realized niche hypervolume, and investigate changes in species' utilization of environmental space through time via generalized linear modelling and bootstrapping of historical values. We also use the "Maxent" algorithm to create and stack contemporary and historical ecological niche models (ENMs) and identify regions where resilience to threatening processes is maximized. Results: We found larger mean reductions in niche hypervolume (39%) than EOO (30.5%), with little correlation ( r  = 0.07) between the two measures, suggesting that contraction of realized niche breadth can be largely independent of reduction in EOO. We also identified a general set of environmental conditions towards which species' realized niches contracted. Comparison of stacked ENMs allowed us to identify regions of natural refuge where environmental conditions are associated with increased species resilience to threats, and conversely, regions where habitat suitability has declined. Main conclusions: Examining species declines from an ecological niche perspective provides a powerful tool for understanding how environmental conditions, biotic interactions and species traits shape responses to local and global environmental changes. Quantifying reductions in niche breadth is crucial as contraction to a narrower subset of environmental space can reduce a species' ability to tolerate other threats and potentially lower adaptive capacity and genetic diversity, increasing extinction risk.